New DNA polymorphism: evidence for a low salt, left-handed form of poly(dG-m5dC). - Feuerstein, B G (1985)
Spectroscopic studies on solutions of poly(dG-m5dC) over a wide range of salt concentration are presented. Low salt solutions [( Na+]) less than 2 mM) of poly(dG-m5dC) produce circular dichroism (CD) spectra typical of the left-handed, Z form at high salt [( Na+] = 1.75 M). Solutions of poly(dG-m5dC) at intermediate salt concentrations, e.g., 142 mM, yield CD spectra characteristic of the right-handed, B conformation. 31p NMR spectra of the low salt form of poly(dG-m5dC) reveal two well separated peaks, split by 1.4 ppm, consistent with a dinucleotide repeat. Kinetic studies show that the transition from the low salt form to teh right-handed B form is slow, as expected for a major conformational change. These results suggest that the Z conformation in poly(dG-m5dC) can be stabilized at very low salt as well as at high salt.